2008
DOI: 10.1080/15228940802152836
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Some Plant Extracts Used in Folk Medicine

Abstract: In the present work, selected plants were screened for their potential antibacterial activity. For evaluating antibacterial activity, both aqueous and organic solvent methanol was used. The plants screened were Ocimum sanctum, Jatropha gossypifolia, Boerhavia diffusa, Azadirachta indica, Solidago virgaurea, and Commelina benghalensis. The antibacterial activity was assessed against six bacterial strains--Pseudomonas testosteroni, Staphylococcus epidermidis, Klebsiella pneumoniae, Bacillus subtilis, Proteus mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(171 citation statements)
references
References 9 publications
7
160
0
4
Order By: Relevance
“…33 It has also been considered that plants and their phytochemical extracts holds great assurance to be used in future medicines as they contain possible sources of antiviral, anti-tumoral and anti-microbial agents. 34,35 Polyphenols were found to be important for research and gains a lot of attention since they were found more effective on human health. 36 Polyphenols and flavonoids are responsible for prevention of various diseases caused by free radicals.…”
Section: Qualitative Phytochemical Screeningmentioning
confidence: 99%
“…33 It has also been considered that plants and their phytochemical extracts holds great assurance to be used in future medicines as they contain possible sources of antiviral, anti-tumoral and anti-microbial agents. 34,35 Polyphenols were found to be important for research and gains a lot of attention since they were found more effective on human health. 36 Polyphenols and flavonoids are responsible for prevention of various diseases caused by free radicals.…”
Section: Qualitative Phytochemical Screeningmentioning
confidence: 99%
“…The present result proves that acetone extract can be employed for the development of formulation for the purification of water from bacteria like Escherichia coli, Vibrio cholerae from diseases like cholera and diarrhoea (Aniel and Naidu, 2011). As it is cleared from the previous literature that extract of organic solvent are much better than aqueous extract for formulation purpose (Nair et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…42 (125 mm) and concentrated using a rotary evaporator (Laborota 4000, SN 090816862, Germany) in a water bath set at 40 °C [8]. The extract was dried in a dessicator over anhydrous CuSO 4 . The powdered residues were transferred into vials and stored pending analysis.…”
Section: Preparation Of Extracts Of Plant Materialsmentioning
confidence: 99%
“…Natural products, either as pure compounds or as standardized plant extracts, provide unlimited opportunities for new drug leads because of the unmatched availability of chemical diversity [3]. Scientific interest in medicinal plant has burgeoned in recent times due to increased efficiency of new plant derived drugs and rising concerns about the side effects of modern medicine, and hence the need to look for new molecular structures as lead compounds from the plant kingdom [2,4].…”
Section: Introductionmentioning
confidence: 99%